A simplified model for fast estimating infrared thermal radiation of low-altitude under-expanded exhaust plumes. (June 2019) - Niu, Qinglin; Fu, Debin; Dong, Shikui; Tan, Heping
Highlights: A time-saving model was proposed for predicting plume's infrared thermal radiations. An assessment of computational error and efficiency was made. Flow properties of plumes in the full domain were examined. Radiation characteristics were obtained numerically. A relationship between the cutoff temperature and plume's length was shown. Abstract: In this paper, a fast estimating method of thermal infrared radiation signatures for low-altitude exhaust plumes was proposed. In engineering application, it is essential to predict the thermal radiation effect of the plume as soon as possible. A simple numerical model was established considering thermal, species formation, entrainment and radiating effects. In this methodology, the mixing region was treated as a hot, under-expanded, reacting and isotonic flow. The reacting flows were simulated by solving the governing equations with finite rate kinetics and conservation matching relations. A single-line-group (SLG) model with Curtis-Godson approximation was utilized to evaluate radiative properties of radiating species. A line-of-sight (LOS) method was used to compute the spectral radiation intensity. This computational model was verified against the Atlas-II's reference data within the wavelengths of 2–6 μm. The simulation analyzed combustion flows and infrared thermal effects of a typical exhaust plume along flight trajectory points. Results show that the current model can dramatically improve the computational efficiency by 100–1000 times by comparing with the commonly used method. According to this model, the plume's range and an appropriable cutoff temperature for thermal radiation calculations are easy to obtain. Infrared radiation phenomena accord with the experimental observations. As a main outcome, this simple model can provide a time-saving and range-unlimited method for the infrared radiation signature prediction of a low-altitude plume in engineering application.